THU0452 Immediate and long term efficacy of anakinra in acute flares due to hydroxyapatite calcifications: a real-life experience of 13 cases. (15th June 2017) - Zufferey, P; Valcov, R; So, A
Abstract : Background: Calcifications composed of hydroxyapatite (HA) crystals can induce acute and severe pain accompanied by signs of acute inflammation. In a previous pilot study, we have shown that anakinra was effective in acute flare of calcific periarthritis of the shoulder in the short term Objectives: The goal of this retrospective observational study was to confirm these results in a larger set of patients, extending the observation to other localizations and to report on the long-term follow-up. Methods: All consecutive patients with an acute flare due to HA deposition and treated with anakinra between March 2011 and November 2016 were included. Flare was defined as symptoms of acute pain at rest present for <10 days. None of the patients had corticosteroid therapy in the last 2 weeks, none had responded to at least 48 hours of high doses of NSAIDs or other rheumatologic diseases explaining the symptoms. Clinical evaluation consisted of patient assessment of pain by VAS (10mm scale) at days 0, 1, 3, 21 and joint mobility. CRP and ESR measurements, ultrasound and x-ray examinations were performed before the treatment and at least once again after the treatment. Anakinra 100mg daily was administered for 1 to 3 consecutive days. Other baseline demographic data and long-term follow up data were collected from the patients' charts and after phone call to the patients Results: 13 patients fulfilled the inclusion criteria. 12 had a flare at the shoulder, 1 at the first MCP of the hand. The acute inclusion flare was the first episode in 9/13 subjects. At baseline, mean pain VAS:8.8/10 Active and passive motion was severely restricted in all patients. Local inflammation was sufficiently severe to induce an elevation of the CRP and ESR in 10/12 patients. By ultrasound, the mean size of calcifications was 17 mm. Only one had an arc-shaped aspect with shadowing, the others were fragmented. Short term follow-up: Pain diminished drastically and rapidly, typically within hours, in most patients after the first injection and was almost absent at day three (mean VAS 1.7/10), stable at 3 weeks (mean VAS: 2.1). At follow-up ultrasound, the calcification disappeared in none of the patients but, in most cases, a reduction (50% mean size reduction) and a fragmentation was observed. Long term follow-up: The median duration was 24 months, (range 4 to 74 months). Only 2/ 12 patients experienced an acute relapse. These two patients already suffered from chronic shoulder pain and had prior flares before the treatment with anakinra. Mild chronic pain, essentially related to movement (mean VAS: 2.7), was still present in 5 patients. Two patients regularly took NSAIDs; the others did not use any painkiller Conclusions: This study suggests that IL-1β inhibition may be an interesting therapeutic approach in acute flares in relation with hydroxyapatite calcification. Moreover this treatment does not seem to be associated with rebound or recurrence of flares in the long term. References: Zufferey P, So AK.A pilot study of IL-1 inhibition in acute calcific periarthritis of the shoulder Ann Rheum Dis. 2013 Mar;72(3):465–7. Disclosure of Interest: None declared